2021
DOI: 10.1002/adfm.202100549
|View full text |Cite
|
Sign up to set email alerts
|

Renal‐Clearable Nickel‐Doped Carbon Dots with Boosted Photothermal Conversion Efficiency for Multimodal Imaging‐Guided Cancer Therapy in the Second Near‐Infrared Biowindow

Abstract: Photothermal agents with absorption in the second near‐infrared (NIR‐II) biowindow have attracted increasing attention for photothermal therapy (PTT) on account of their deeper tissue penetration capacity. However, most of the current NIR‐II photothermal agents exhibit low photothermal conversion efficiency (PCE) and long‐term biotoxicity. To overcome these shortcomings, herein, nickel and nitrogen co‐doped carbon dots (Ni‐CDs, ≈4.6 nm) are prepared via a facile one‐pot hydrothermal approach for imaging‐guided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(112 citation statements)
references
References 71 publications
2
110
0
Order By: Relevance
“…It has been reported that glomerular filtration by the kidneys is highly size-selective [40,41]. Previous in vivo biodistribution studies of single carbon dots with a diameter less than 10 nm proved that the kidneys were the main clearance organ [42][43][44]. Our results indicate that the CDs@PEI nanoparticles with approximately 100 nm in diameter could be excreted from the intestine in the feces.…”
Section: In Vivo Clearance Of Cds@pei Nanoparticlessupporting
confidence: 55%
“…It has been reported that glomerular filtration by the kidneys is highly size-selective [40,41]. Previous in vivo biodistribution studies of single carbon dots with a diameter less than 10 nm proved that the kidneys were the main clearance organ [42][43][44]. Our results indicate that the CDs@PEI nanoparticles with approximately 100 nm in diameter could be excreted from the intestine in the feces.…”
Section: In Vivo Clearance Of Cds@pei Nanoparticlessupporting
confidence: 55%
“…In addition, the stability of the specimens during the four repeated laser on-off cycles was also evaluated. As a result, the photothermal conversion efficiency was calculated as follows [ 30 , 31 ]: where T max,spe denotes the maximum temperature of tested specimens; T max, water denotes the maximum temperatures of water; I denotes the laser power; A 808 is the absorbance value of tested specimen aqueous solution at 808 ​nm; m i denotes the water mass; C p,i denotes the water heat capacity; θ is the system constant.…”
Section: Methodsmentioning
confidence: 99%
“…[28] The excellent optical properties and red/near-infrared absorption properties can enable CDs to provide higher penetration depth and lower phototoxicity in tissues, and meanwhile, red/near-infrared absorption can make CDs generate higher heat under lower power density laser irradiation, which can be used for photothermal therapy and targeted killing of tumor cells. [29,30] In addition, after absorbing light, some CDs can also be sensitized as photosensitizers, undergo electron/energy transfer reactions, and generate reactive oxygen species for photodynamic therapy. [31,32] The available studies demonstrate that CDs exert direct therapeutic effects in vitro and in vivo, and that they can potentially cure Parkinson's disease and various cancer.…”
Section: Introductionmentioning
confidence: 99%